Validation of a Paediatric Early Warning Score through clinical audit and analysis of nursing attitudes - Joyce, Carly (2012)
Paediatric early warning score (PEWS) tools are becoming commonplace to aid the routine assessment of inpatient illness severity. This is part of a wider national strategy to recognise and respond to clinical deterioration early. However tools currently in use vary in assessment criteria. This study aims to assess the validity of a PEWS tool within a local NHS Trust. Methodology Two methodological approaches are used to assess the validity of the local PEWS. Audit Clinical audit is used to assess the extent of criterion related validity within the PEWS. Information is also gathered upon the frequency and accuracy of PEWS documentation. Questionnaire A staff questionaire is also conducted to gather nurse attitudes towards the local tool; their perspectives upon the face validity, the readability and the content validity of the tool are assessed. Nurses are also questioned on their desire for additional support from a paediatric CCOT in the event of clinical deterioration. Results Audit 77 patient notes were reviewed, in which a total of 1188 observation sets were recorded. It was found that blood pressure and pain assessment are poorly recorded (8.2% and 59.5% respectively), although, excluding the latter, observations were well recorded within the local trust (>73%). High levels of criterion related validity were found; on only four occasions did the level of staff concern not correlate with the PEWS. Questionnaire One third (n=50) of the total population of children’s nurses working in the local Trust completed study questionnaires. High levels of face validity, readability and content validity were found through responses and the majority of nurses expressed a desire for a paediatric CCOT. Conclusion Although the study findings are complementary towards the local PEWS tool, it was also found that experiential knowledge plays a large role in the detection of serious illness in children; the use of the local PEWS tool should not undermine this fact.